Reasons to revive the National Pact for the strengthening of Secondary Education in the midst of curriculum reform in Brazil (Research, Society and Development, 2023)
The educational legislation is modified periodically based on different factors and interests present in society. An attempt to reform the Brazilian High School is underway, even though it has been the target of numerous criticisms. Around this theme, this work aims to list aspects of the National Pact for the Strengthening of Secondary Education (PNEM) that could be useful at this time of discussion about curricular changes: either to completely deny the proposed proposal, a position defended here, or to change specific points of the text. This study is characterized as documentary and literature review, being produced in a qualitative approach. The original project document was analyzed, as well as reference articles searched on the journal portal of the Coordination for the Improvement of Higher Education Personnel on texts that listed the benefits perceived in the PNEM that could be useful in the current context. In general, the highlighted arguments were: re-signification of the teaching profession; qualification of the choice of textbook; basis for teaching in new curricular possibilities; reflection on professional education. The PNEM is not a magic formula that will overcome the challenges imposed by the current situation. But the fact is that without a more qualified look and teaching action, such improvements will hardly be achieved.